Analysis of Utility Approaches in Accounting Reporting Decision Making - Adi Gilar Nugraha; Aqila Daffa Hakimah; Lia Uzliawati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This paper examines the practices of financial reporting within corporations. Through meticulous preparation of records, bookkeeping, and detailed reporting of business activities, management can effectively oversee business developments. In this context, financial reports serve as a crucial tool for evaluating and monitoring a company’s financial performance over a specific period, particularly when employing a decision-usefulness approach. To fully grasp this concept, it is essential to explore other relevant economic and financial theories. For accountants, understanding how to enhance the utility of financial statements and the concept of